Perfusion of Brain Preautonomic Areas in Hypertension: Compensatory Absence of Capillary Rarefaction and Protective Effects of Exercise Training - Jordão, Maria Tereza; Ceroni, Alexandre; Michelini, Lisete C. (Frontiers in Physiology, 2021)
Capillary rarefaction and deleterious arteries’ remodeling are characteristic hallmarks of hypertension that are partially corrected by exercise training. Experimental evidence also showed capillary rarefaction within brain cortex and reduced cerebral blood flow. There is no information on hypertension- and exercise-induced effects on capillary profile and function within preautonomic nuclei. We sought now to evaluate the effects of hypertension and exercise training (T) on capillary network within hypothalamic paraventricular (PVN) and solitary tract (NTS) nuclei, and on brain arteries’ remodeling. Age-matched SHR and WKY, submitted to moderate T or kept sedentary (S) for 3 months, were chronically cannulated for hemodynamic recordings at rest. Rats were anesthetized for iv. administration of FITC-dextran (capillary volume/density measurements) or 4% paraformaldehyde perfusion (basilar, middle, and posterior arteries’ morphometry) followed by brain harvesting and processing. Other groups of conscious rats had carotid blood flow (CBF, ultrasound flowmeter) acquired simultaneously with hemodynamic recordings at rest and exercise. SHR-S exhibited elevated pressure and heart rate, reduced CBF, increased arteries’ wall/lumen ratio, but no capillary rarefaction within the PVN and NTS. T improved performance gain and caused resting bradycardia in both groups; pressure and sympathetic vasomotor activity falls and normalization of the wall/lumen ratio were only observed in SHR-T. T groups responded with marked PVN and NTS capillary angiogenesis and augmented CBF during exercise; to avoid overperfusion at rest, reduced basal CBF was observed only in WKY-T. Data indicated that absence of SHR-S capillary rarefaction and the intense SHR-T angiogenesis within autonomic areas associated with correction of deleterious arteries’ remodeling are essential adjustments to hypertension and exercise training, respectively. These adaptive responses maintain adequate baseline perfusion in SHR-S and SHR-T preautonomic nuclei, augmenting it in exercised rats when a well-coordinated autonomic control is required.